Development of high-throughput multi-residue method for non-steroidal anti-inflammatory drugs monitoring in swine muscle by LC-MS/MS. Issue 7 (2nd July 2016) - Castilhos, Tamara S.; Barreto, Fabiano; Meneghini, Leonardo; Bergold, Ana Maria
ABSTRACT: A reliable and simple method for the detection and quantification of residues of 14 non-steroidal anti-inflammatory drugs and a metamizole metabolite in swine muscle was developed using liquid chromatography-electrospray ionisation-tandem mass spectrometry (LC-ESI-MS/MS). The samples were extracted with acetonitrile (ACN) in solid–liquid extraction followed by a low-temperature partitioning (LLE-LTP) process at –20 ± 2°C. After evaporation to dryness, the residue was reconstituted with hexane and a mixture of water:acetonitrile (1:1). LC separation was achieved on a reversed-phase (RP18 ) column with gradient elution using water (phase A) and ACN (phase B) both containing 1 mmol l – 1 ammonium acetate (NH4 COO) with 0.025% acetic acid. Analysis was carried out on a triple-quadrupole tandem mass spectrometer (LC-MS/MS) in multiple reaction monitoring mode using an electrospray interface in negative and positive mode in a single run. Method validation was performed according to the criteria of Commission Decision No. 2002/657/EC. The matrix effect and linearity were evaluated. Decision limit (CCα), detection capability (CCβ), accuracy and repeatability of the method are also reported. The proposed method proved to be simple, easy and adequate for high-throughput analysis and was applied to routine analysis by the Brazilian Ministry of Agriculture, Livestock and Food Supply. Graphical Abstract: